A Green Biocompatible Fabrication of Highly Porous Functional Ceramics with High Strength and Controllable Pore Structures. Issue 8 (August 2016) - Xu, Changlu; Liu, Haoran; Yang, Huilin; Yang, Lei
Abstract : A green biocompatible foaming method utilizing natural coconut oil and cornstarch was developed to fabricate highly porous functional ceramics with controllable strengths and pore structures. The porosity of Al2 O3 ceramics prepared via this method reached 79.6%–86.9% while these ceramics maintained high compressive strengths of 2.2–5.5 MPa. More importantly, porous Al2 O3 ceramic with a pore size gradient was also readily fabricated by casting serial layers of foams that were set for different time periods. The potential applications of porous Al2 O3 and HA ceramics fabricated by this green foaming method including scaffolds for oil cleaning and cell culture, respectively, were also demonstrated.